O marinheiro negro Marcílio Dias: as muitas memórias de um cidadão exemplar - Álvaro Pereira do Nascimento (Navigator)
This article focus on the Marcilio Dias’ life in the Brazilian Navy, from recruitment until his death at the Battle of Riachuelo, after ten years of military service. It also analyzes how the history of his bravery in the war was spread, thus becoming a venerated memory and remembered pedagogically for civilian and military students.